An analysis of the relation between natural disasters and Big Data. (2016) - Velev, Dimiter; Zlateva, Plamena
Nowadays the combination of several major ICT developments form a trend to a more effective management of natural disasters - social networking, mobile computing, Internet of Things and Cloud computing. The combination of these ICT technologies leads to the fact that rescue organisations are trying ways to find value in and insight from both structured and unstructured data from internal and external sources, generated in large volumes. New technology and software tools are needed for handling this and the answer is Big Data. The purpose of this paper is to investigate and analyse the relation between natural disasters and Big Data.